Controlled assembly of hybrid architectures based on carboxylic acid ligands and [(O3PCH2PO3)Mo6O22]12−. Issue 40 (1st April 2015) - Sun, Xiaopeng; Yang, Donghui; Wang, Gaigai; Liang, Zhijie; Ma, Pengtao; Wang, Jingping; Niu, Jingyang
Abstract : Polyanion2a with a reverse symmetrical "crown-type" structure is composed of two (HO3 PCH2 PO3 )Mo6 O18 (CH3 CO2 )2 subunits and a linking bridge. Abstract : The nature of carboxylic acid has a profound effect on constructing POM-based architectures. With different carboxylic acid ligands, three novel diphosphonate-containing compounds have been synthesized and further investigated by elemental analyses, single-crystal X-ray diffraction, IR spectroscopy, UV-vis spectroscopy, X-ray powder diffraction (XRPD), 31 P NMR spectroscopy, cyclic voltammetric behavior and thermogravimetric (TG) analyses. [(HO3 PCH2 PO3 )Mo6 O18 (O2 CC6 H4 OH)2 ] 5− (1a ) shows a ring-shaped cluster with a Mo6 plane framework. [(HO3 PCH2 PO3 )Mo6 O18 (CH3 CO2 )2 2 Na2 (H2 O)2 ] 8− (2a ) is a reverse symmetrical "crown-type" structure and the subunits are linked by two Na–O(1W)–Na bridges. The polyanion [(O3 PCH2 PO3 )(Mo6 O18 (H2 O)2 )(O2 CCH2 CO2 )2 (Mo2 O5 )2 (μ3 -O)2 ] 12− (3a ) appears as an "S-shaped" structure with a centre of inversion.